Human Leukocyte Antigen HLA-DRB1 Determinants Susceptibility to Gastroesophageal Reflux Disease - Mahdi, Batool Mutar; Hasan, Riyadh Mohamad; Hazim, Wafaa (Journal of Medicine, 2017)
Background: Gastro oesophageal reflux disease (GERD) is characterized by diverse symptoms. There is an evidence for a genetic component to Gastro oesophageal reflux disease as supported by familial aggregation of this disease. Aim of the study was to investigate whether certain human leucocyte antigen genes HLA-DRB1 are associated with (GERD). Methods: Patients and controls were prospectively recruited from GIT center at Al-Kindy Teaching Hospital (Baghdad-Iraq) between January 2014 and July 2016. Sixty Iraqi Arab Muslim patients with a history of heartburn and dyspepsia were compared with 100 Iraqi Arab Muslims controls. All study patients and control groups underwent upper gastrointestinal endoscopic examinations and their serums were analyzed for CagA antibodies Immunoglobulin G (IgG) for H. pylori. HLA-DRB1 genotyping were done to both groups. Results: A total of 60 patients with erosive gastritis; GERD (Grade II and III) were evaluated, together with 100 controls. There is a significant increase of H. pylori infection (p=0.0001) in GERD patients than control group. HLA-DRB1* 15: 01was significantly increased in GERD patients in comparison with control group and an increased frequency of HLADRB1*11: 01 in control group compared with patients group. Conclusions: There is an association between HLA-DRB1 *15: 01 in GERD patients with H pylori positive patients. J MEDICINE Jan 2018; 19 (1) : 3-9